Pengaruh Kinerja Lingkungan Terhadap Kinerja Keuangan Dengan Corporate Social Responsibility Sebagai Variabel Intervening - Eliana Ilyas; Nurhayati; Alfira Ayudia Putri; Nasri Zarman (Jurnal Ilmiah Mahasiswa Ekonomi dan Bisnis Islam, 2022)
This study aims to examine the effect of environmental performance on financial performance with corporate social responsibility as an intervening variable in textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange. This research is a type of causal associative research with a quantitative approach. The population of this study are manufacturing companies in the textile and garment sub-sector which are listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sample of this research is 32 companies selected by using purposive sampling method. The data used is secondary data, and the amount of data obtained is 90 data studied. The data analysis method used to test the hypothesis is panel data regression with the help of the Eviews program version 10.0, with the data collection method used is the documentation method obtained through the official website of the Indonesia Stock Exchange (www.idx.co.id) and the respective official websites each company as well as the official website of the Ministry of Environment and Forests (www.menlhk.go.id). the results of the study concluded that (1) Environmental Performance has a significant effect on Financial Performance, (2) Environmental Performance has a significant effect on Corporate Social Responsibility, (3) Corporate Social Responsibility has a significant effect on Financial Performance, (4) Environmental performance has a significant effect on financial performance by Corporate Social Responsibility as an intervening variable. The results of this study indicate that environmental performance with regard to corporate social responsibility is very important to be implemented in companies, because it can improve the company's financial performance.